2011
DOI: 10.1158/1078-0432.ccr-11-0127
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Aberrations Leading to MAPK Pathway Activation Mediate Oncogene-Induced Senescence in Sporadic Pilocytic Astrocytomas

Abstract: Purpose: Oncogenic BRAF/Ras or NF1 loss can potentially trigger oncogene-induced senescence (OIS) through activation of the mitogen-activated protein kinase (MAPK) pathway. Somatic genetic abnormalities affecting this pathway occur in the majority of pilocytic astrocytomas (PA), the most prevalent brain neoplasm in children. We investigated whether OIS is induced in PA.Experimental Design: We tested expression of established senescence markers in three independent cohorts of sporadic PA. We also assessed for O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 47 publications
3
98
0
2
Order By: Relevance
“…BRAF V600E mutations occur in tumors that differ greatly in biologic aggressiveness, including melanoma, papillary thyroid cancer, Langerhans cell histiocytosis, pilocytic astrocytoma, and melanocytic nevi [43][44][45][46][47]. In indolent tumors, the BRAF V600E mutation is thought to induce senescence through a mechanism that involves the tumor suppressor gene p16 (INK4a) [48,49]. Although we did not study p16 in our series, all metanephric adenomas studied by Choueiri et al [27] demonstrated nuclear p16 immunoreactivity.…”
Section: Discussionmentioning
confidence: 76%
“…BRAF V600E mutations occur in tumors that differ greatly in biologic aggressiveness, including melanoma, papillary thyroid cancer, Langerhans cell histiocytosis, pilocytic astrocytoma, and melanocytic nevi [43][44][45][46][47]. In indolent tumors, the BRAF V600E mutation is thought to induce senescence through a mechanism that involves the tumor suppressor gene p16 (INK4a) [48,49]. Although we did not study p16 in our series, all metanephric adenomas studied by Choueiri et al [27] demonstrated nuclear p16 immunoreactivity.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, the loss of expression of the neighbor gene p16 has a prognostic impact on PAs [19] . Recently, it was described that the simultaneous loss of expression of p16 and MTAP determines shorter survival of patients with non-small-cell lung cancer [45] .…”
Section: Discussionmentioning
confidence: 94%
“…Oncogene-induced senescence restricts the progression of benign tumors, such as melanocytic nevi and PAs, in response to V600E BRAF mutation [19,24] . In PAs, the ectopic expression of the V600E BRAF mutation results in induction of the INK4a/ ARF locus, at 9p21, with subsequent overexpression of p16 , a known senescence marker [19,25] , the loss of expression of which correlates with a shorter overall survival (OS) in sporadic PAs [19] and a more aggressive course in some Nf1-PAs [26] .…”
Section: Introductionmentioning
confidence: 99%
“…Although f-BRAF can transform NIH3T3 cells (Jones et al 2008), previous studies have demonstrated that BRAF does not increase astrocyte proliferation (Jacob et al 2009), induces senescence of astrocytes (Jacob et al 2011) and neural stem cells (NSCs) in vitro (Raabe et al 2011), and does not result in gliomagenesis when ectopically expressed in mouse brains in vivo (Robinson et al 2010).…”
mentioning
confidence: 99%